2017
DOI: 10.1038/s41598-017-12720-w
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Low-Dose Alcohol Consumption on Inflammation Following Transient Focal Cerebral Ischemia in Rats

Abstract: Increasing evidence suggest that low-dose alcohol consumption (LAC) reduces the incidence and improves the functional outcome of ischemic stroke. We determined the influence of LAC on post-ischemic inflammation. Male Sprague-Dawley rats were divided into 3 groups, an ethanol (13.5% alcohol) group, a red wine (Castle Rock Pinot Noir, 13.5% alcohol) group, and a control group. The amount of alcohol given to red wine and ethanol groups was 1.4 g/kg/day. After 8 weeks, the animals were subjected to a 2-hour middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Interestingly, our data and the recently published data on the beneficial effect of low-dose alcohol consumption on inflammation following transient focal cerebral ischemia in rats (7) suggest that, similarly to the biphasic effects of alcohol on the risk of ischemic stroke (2), alcohol consumption also could have a biphasic effect on the consequences of ischemic stroke. These data, thus, help to clarify the apparently controversial clinical results found on the impact of alcohol consumption on stroke (4,5).…”
Section: Alcohol Exposure Alters the Gene Expression Of Inflammatorsupporting
confidence: 68%
See 1 more Smart Citation
“…Interestingly, our data and the recently published data on the beneficial effect of low-dose alcohol consumption on inflammation following transient focal cerebral ischemia in rats (7) suggest that, similarly to the biphasic effects of alcohol on the risk of ischemic stroke (2), alcohol consumption also could have a biphasic effect on the consequences of ischemic stroke. These data, thus, help to clarify the apparently controversial clinical results found on the impact of alcohol consumption on stroke (4,5).…”
Section: Alcohol Exposure Alters the Gene Expression Of Inflammatorsupporting
confidence: 68%
“…Current clinical studies are controversial and have described either an aggravating effect (4) or no effect of HD (5) on stroke severity. Preclinical reports have also described either a protective effect of low alcohol consumption on ischemic stroke (6,7) or larger infarcts in rodents exposed to higher alcohol dose (6,8). However, the mechanisms mediating this aggravation are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The real infarct volume (cortex, striatum and hemisphere), after excluding edema, was calculated by subtraction of the ipsilateral non-infarcted regional volume from the contralateral regional volume. The real infarct volume was then divided by the contralateral regional volume as a percent of the contralateral region (McCarter et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…A plethora of studies have reported that alcohol consumption is detrimental to health and contributes to cognitive deficits and neurodegeneration (Crews and Nixon, 2009) and increases the risk of developing neurodegenerative disorders such as AD (Harwood et al, 2010) and PD (Liu et al, 2013). On the contrary, a growing number of contemporary findings have addressed low to moderate consumption of alcohol to have neuroprotective effects (McCarter et al, 2017) and reduces the risk associated with neurodegenerative disorders (Liu et al, 2013;Zhang D. et al, 2014). Various factors were reported to determine the neuroprotective and neurodegenerative properties of alcohol, including the types of beverage consumed (beer vs wine vs liquor), amount of alcohol intake, blood alcohol level (low vs moderate vs high), nutrient deficiency and genetic components.…”
Section: Alcohol: Could It Be Neuroprotective?mentioning
confidence: 99%